PENGARUH VARIASI EMULGATOR KRIM ANTIOKSIDAN KOMBINASI EKSTRAK DAUN PUTRI MALU (MIMOSA PUDICA LINN.) DAN DAUN SALAM (SYZYGIUM POLYANTHUM) SECARA IN VITRO - Naman, Putri Ekawani Melianthi; Rejeki, Endang Sri; Aisyah, Siti (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2024)
Putri Malu (Mimosa pudica Linn.) and Salam (Syzygium polyanthum) contain flavonoid that have antioxidant activity. This study aims to determine the effect of variations of tween 80 and span 80 on the physical quality of the cream and to determine the antioxidant activity of the combination cream of Putri Malu and Salam leaves. The study used the extracts of Putri Malu and Salam leaves which were macerated with ethyl acetate. The cream was made in 6 formulas with variations of emulsifier tween 80 3%, 4% and 5% and span 80 7%, 6% and 5%. Antioxidant cream was tested for physical quality and antioxidant activity and then analyzed by SPSS method. Based on statistics, variations in the concentration of tween 80 and span 80 affect the physical quality and stability of the combination cream of Putri Malu and Salam leaves extracts. The combination cream has antioxidant activity that is in the weak category. The formula with 3% tween 80 and 7% span 80 concentration had the best physical quality and the cream formula with 3% and 7%, 4% and 6%, and 5% and 5% concentration respectively had the best antioxidant activity which was not significantly different from the positive control cream.